Pelatihan Desain Pembelajaran Kreatif dan Menyenangkan MI Miftahul Ulum - Yusuf Effendi, Muhammad; Salamah, Evi Rizqi; Dwi Rochmaniah, Desty (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
The profession of SD/MI teachers as professional educators who act as facilitators in learning requires their creativity to explore the potential of learning resources and media in their environment in order to teach their students in a quality manner. In order to become a good facilitator, elementary school teachers are expected to be able to equip themselves with insight and skills in developing the design and creation of learning media so that teachers can carry out their role well. The reality shows that MI teachers in Jombok sub-district, Jombang Regency generally experience difficulties in improving the quality and effectiveness of learning in their respective elementary schools. This situation is caused by a lack of knowledge, creativity, knowledge possessed by teachers and the facilities and infrastructure in schools are unable to support students' activeness and enjoyment in learning. Teachers lack insight and skills in designing creative learning, and making students active and enjoyable in learning. Therefore, supervisors and school principals at MI Miftahul Ulum are holding creative and fun learning design training for MI teachers in Jombok District, Jombang Regency with the hope of increasing the effectiveness and quality of the learning process at MI Miftahul Ulum and ultimately supporting the achievement of educational goals.